Resolution 819 - Battiato, Giacomo (France, 2008)
"Resolution 819" tells the compelling story of a young investigator sent to Bosnia in 1995 to investigate the disappearance of 8,000 men in Srebrenica and eventually bring the perpetrators of the massacre to justice at the International Criminal Court. Benoît Magimel stars as Jacques Calvez, a man of integrity who refuses to let politicians, mobsters or bureaucrats stand in his way. He receives valuable help in his quest from Lherbier (Hippolyte Girardot), a French secret service agent, and above all from beautiful forensic anthropologist Clara Gorska (Karolina Gruszka).